Pengaruh Manajemen Pembelajaran terhadap Perkembangan Motorik Anak Usia Dini - Ade Nurcahyani Ritonga; Afrah Nadihilah Hasibuan; Annisa Zahra Manullang; Eka Riskin Pitriana; Khoiriyah Anggina Br Lubis; Riska Anita Siregar; Yuli Anisah Hasibuan (Badan Penerbit STIEPARI Press, 2025)
Motor development is one of the fundamental aspects of early childhood growth that includes the ability to control body movements, coordination, and physical skills that are the basis for later cognitive and social-emotional development. This study aims to analyze the influence of learning management on the optimization of motor development in early childhood, focusing on how systematic planning, implementation, and evaluation of learning can improve children's gross and fine motor skills. Through a qualitative approach with in-depth observation methods, structured interviews with educators, and documentation studies, this study examines the implementation of learning management in various early childhood education institutions. This study explores how effective learning management strategies can stimulate various aspects of children's motor development, including bilateral coordination, postural balance, fine movement control, muscle strength, and sensory-motor integration. The results of the study show that the implementation of good learning management has a significant positive impact on improving early childhood motor skills. Children who received systematic management learning showed improvements in eye-hand coordination, core stability, postural control, movement accuracy, and the ability to follow complex motor instructions.